The risk of being depressed is significantly higher in cancer patients than in the general population: Prevalence and severity of depressive symptoms across major cancer types. (February 2017) - Hartung, T.J.; Brähler, E.; Faller, H.; Härter, M.; Hinz, A.; Johansen, C.; Keller, M.; Koch, U.; Schulz, H.; Weis, J.; Mehnert, A.
Abstract: Background: Depression is a common co-morbidity of cancer that has a detrimental effect on quality of life, treatment adherence and potentially survival. We conducted an epidemiological multi-center study including a population-based random comparison sample and estimated the prevalence of depressive symptoms by cancer site, thereby identifying cancer patients with the highest prevalence of depression. Patients and methods: We included 4020 adult cancer inpatients and outpatients from five distinct regions across Germany in a proportional stratified random sample based on the nationwide cancer incidence and a comparison group consisting of 5018 participants. Both groups reported depressive symptoms by filling in the Patient Health Questionnaire (PHQ-9). In multivariate analyses adjusted for age and sex, we calculated the odds of being depressed. Results: Out of 5818 eligible patients, 69% participated (51% women, mean age = 58 years). We estimated that one in four cancer patients (24%) is depressed (PHQ-9 ≥ 10). The odds of being depressed among cancer patients were more than five times higher than in the general population (OR, 5.4; 95% CI, 4.6–6.2). Patients with pancreatic (M = 8.0, SD = 5.0), thyroid (M = 7.8, SD = 6.3) and brain tumours (M = 7.6, SD = 4.9) showed the highest prevalence, whereas patients with prostate cancer (M = 4.3, SD = 3.8) and malignant melanoma (M = 5.3, SD = 4.3) had the lowest levels of depressive symptoms. Conclusion: Our results help clinicians identify cancer patients in need of psychosocial support when navigating in the growing survivor population. Highlights: One in four cancer patients is depressed. The odds of being depressed are five times higher in cancer patients. People with brain tumours and thyroid cancer were the most depressed.